2013
DOI: 10.2174/1876817220130613001
|View full text |Cite
|
Sign up to set email alerts
|

Benzene-Poly-Carboxylic Acids Complex with Cis-Diammineplatinum (II) Dichloride in the Treatment of Stage IV Breast Cancer Patients

Abstract: An anti-cancer agent containing benzene-poly-carboxylic acids complex with cis-diammineplatinum (II) dichloride (BP-C1) was developed to establish a low toxic and cost effective treatment of breast cancer. The study was aimed to investigate if BP-C1 could be given continuously without rest periods and to estimate Maximum Tolerated (MTD) and Minimum Efficient Dose (MED) in metastatic breast cancer (MBC) treatment. A non-randomized, multicentre trial with 3-level Response Surface Pathway design was performed. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…The CBPDA has been tested in clinical trials and has shown to exert anti-tumor activity in breast cancer patients stage IV [13][14][15][16]. To understand whether this anti-tumor activity is associated with a direct effect on tumor cells and/or indirectly through activation of the immune system, we have tested the effect of CBPDA on human peripheral mononuclear cells comprising lymphocytes and monocytes, as well as cytotoxic lymphocytes with specificity to tumor cells [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CBPDA has been tested in clinical trials and has shown to exert anti-tumor activity in breast cancer patients stage IV [13][14][15][16]. To understand whether this anti-tumor activity is associated with a direct effect on tumor cells and/or indirectly through activation of the immune system, we have tested the effect of CBPDA on human peripheral mononuclear cells comprising lymphocytes and monocytes, as well as cytotoxic lymphocytes with specificity to tumor cells [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Platin has been used in several efficient 2 nd line schemes such as RICE studied in pediatric patients [11] and in adults [39]. The new substance CDBPA has been developed for treatment of solid as well as hematological tumors due to its strong immune-modulatory effects besides its cytostatic effects which has been shown to reduce the occurrence of adverse events and decreasing the toxicity of the cancer disease itself, thereby improving the quality of life especially in stage IV breast cancer patients [13][14][15][16]. Thus the authors advocate that CDBPA due to its immune-modulatory effects should be used in 2 nd line therapies instead the current used platin drugs to spare the patients for adverse effects, toxicity and to improve the quality of life for these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first patient in the sequence receives the predefined starting dose. 10,14 The response from this patient determines the dose for the second patient in the same sequence. In general, the response from the patient at design level i (1≤ i ≤ n) determines the dose for the patient at the next design level i + 1.…”
Section: Rsp Designmentioning
confidence: 99%
“…The response surface pathway (RSP) design was published under this name for the first time in 2013. 3,4 However, the philosophy behind the model was launched back in 2001. 5 In the medical and biological field, the lack of stochastic approach dominates study designs.…”
mentioning
confidence: 99%